2018
DOI: 10.1186/s42358-018-0021-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of falls in adults with established rheumatoid arthritis and associated factors

Abstract: Background: Rheumatoid arthritis patients may have an increased risk of falls due to changes caused by the disease such as muscle weakness, joint impairment, reduced mobility and postural instability. The aim of this study was to prospectively analyze the occurrence of falls in RA patients and its risk factors. Methods: A cohort of 86 RA patients were assessed over 1 year for disease activity using the Disease Activity Score (DAS-28), for functionality using the Health Assessment Questionnaire (HAQ), for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(79 reference statements)
5
6
2
2
Order By: Relevance
“…Physical performance tests such as SPPB, including gait speed and chair rise test did not reveal significant differences between fallers and non-fallers and were also not significant predictors for falls in the univariate analyses. These results reflect those of Lourenco et al [50], who also found no prospective association of SPPB with falls in patients with RA. Gait speed alone was also a superior predictor to SPPB in the cross-sectional study by Dietzel et al [53].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Physical performance tests such as SPPB, including gait speed and chair rise test did not reveal significant differences between fallers and non-fallers and were also not significant predictors for falls in the univariate analyses. These results reflect those of Lourenco et al [50], who also found no prospective association of SPPB with falls in patients with RA. Gait speed alone was also a superior predictor to SPPB in the cross-sectional study by Dietzel et al [53].…”
Section: Discussionsupporting
confidence: 91%
“…Since this was a population with low RA disease activity, it might not be surprising that the association with disease activity was not demonstrated. The RA disease duration has been described by numerous studies as a non-significant factor for falls [6,7,12,50]. This is also supported by the present study results showing no association with falls and duration of disease or disease activity (DAS28 CRP ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Fall prevalence in patients with SpA ranged between 13% 11 to 25.4% 9 across the 3 studies, and appears to be largely similar to patients with rheumatoid arthritis (RA) (range between 10% to 43%). 15,20 Patients with RA often have peripheral joint arthritis, and this can affect their mobility and impose postural instability, 20 which can similarly affect SpA patients with peripheral arthritis, which has been known to affect 30% of patients with SpA. 10 Despite patients with SpA being generally younger, prevalence of falls in patients with SpA was also largely similar to that in the older adult population which ranged from 17.2% in Singapore 21 to 42.4% in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…First, edema is a strong risk factor for hospitalization [50] and skin tear development [51]. Second, immunosuppressed patients have an increased risk of falls due to disease or treatment-related consequences such as muscle weakness, joint impairment, reduced mobility and postural instability [52]. Third, involuntary movements and muscle weakness are common in patients with neurodegenerative diseases, increasing the risk of aspiration due to swallowing dysfunction [53].…”
Section: Plos Onementioning
confidence: 99%